Heterogeneity of the Left Temporal Lobe in Semantic Representation and Control: Priming Multiple versus Single Meanings of Ambiguous Words - Whitney, Carin (Oxford University Press, 2011)
Semantic judgments involve both representations of meaning plus executive mechanisms that guide knowledge retrieval in a task-appropriate way. These 2 components of semantic cognition—representation and control—are commonly linked to left temporal and prefrontal cortex, respectively. This simple proposal, however, remains contentious because in most functional neuroimaging studies to date, the number of concepts being activated and the involvement of executive processes during retrieval are confounded. Using functional magnetic resonance imaging, we examined a task in which semantic representation and control demands were dissociable. Words with multiple meanings like “bank” served as targets in a double-prime paradigm, in which multiple meaning activation and maximal executive demands loaded onto different priming conditions. Anterior inferior temporal gyrus (ITG) was sensitive to the number of meanings that were retrieved, suggesting a role for this region in semantic representation, while posterior middle temporal gyrus (pMTG) and inferior frontal cortex showed greater activation in conditions that maximized executive demands. These results support a functional dissociation between left ITG and pMTG, consistent with a revised neural organization in which left prefrontal and posterior temporal areas work together to underpin aspects of semantic control.